Landscape composition and life‐history traits influence bat movement and space use: Analysis of 30 years of published telemetry data. Issue 12 (3rd October 2021) - Laforge, Alexis; Archaux, Frédéric; Coulon, Aurélie; Sirami, Clélia; Froidevaux, Jérémy; Gouix, Nicolas; Ladet, Sylvie; Martin, Hilaire; Barré, Kevin; Roemer, Charlotte; Claireau, Fabien; Kerbiriou, Christian; et al.
Abstract: Aim: Animal movement determines home range patterns, which in turn affect individual fitness, population dynamics and ecosystem functioning. Using temperate bats, a group of particular conservation concern, we investigated how morphological traits, habitat specialization and environmental variables affect home range sizes and daily foraging movements, using a compilation of 30 years of published bat telemetry data. Location: Northern America and Europe. Time period: 1988–2016. Major taxa studied: Bats. Methods: We compiled data on home range size and mean daily distance between roosts and foraging areas at both colony and individual levels from 166 studies of 3, 129 radiotracked individuals of 49 bat species. We calculated multi‐scale habitat composition and configuration in the surrounding landscapes of the 165 studied roosts. Using mixed models, we examined the effects of habitat availability and spatial arrangement on bat movements, while accounting for body mass, aspect ratio, wing loading and habitat specialization. Results: We found a significant effect of landscape composition on home range size and mean daily distance at both colony and individual levels. On average, home ranges were up to 42% smaller in the most habitat‐diversified landscapes while mean daily distances were up to 30% shorter in the most forested landscapes. Bat home range size significantly increased with body mass, wing aspect ratio and wing loading, and decreased with habitat specialization. Main conclusions: Promoting bat movements through the landscape surrounding roosts at large spatial scales is crucial for bat conservation. Forest loss and overall landscape homogenization lead temperate bats to fly further to meet their ecological requirements, by increasing home range sizes and daily foraging distances. Both processes might be more detrimental for smaller, habitat‐specialized bats, less able to travel increasingly longer distances to meet their diverse needs.